Experimental wavelet transient-state analysis of electrical machines directly feeding by photovoltaic cells - KIYAK, İSMAİL (My University, 2009)
This work describes an experimental wavelet packet transient state analysis for educational purposes. The study particularly deals with electrical machines directly fed by photovoltaic cells. In a PV system design, the selection and proper installation of appropriatelysized components directly affects system reliability, lifetime and initial cost. In any installation, one must keep in mind that trade-ojjs are necessary in system design and component selection. In this study, the startup and nominal operating behaviors of electrical machines directly connected to a photovoltaic system (not having any storage or control system) were empirically examined. The power values obtained (in p.u.) were decomposed to sub-frequency components by means of the discrete wavelet packet transformation then they were compared to each other.
Keywords: Elektrik-Elektronik Mühendisliği; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences; Photovoltaic Cells; Transient State; Electrical Machines; Wavelet Filter Bank; Wavelet Packet Transform